Nephrotoxicity of Calcineurin Inhibitors in Kidney Epithelial Cells is Independent of NFAT Signaling - Karolin, Andrea; Escher, Geneviève; Rudloff, Stefan; Sidler, Daniel (Frontiers in Pharmacology, 2022)
Background: Calcineurin inhibitors (CNI) such as Cyclosporine A (CsA) and Tacrolimus (FK506) are commonly used after renal transplantation in order to suppress the immune system. In lymphoid cells, CsA acts via the Calcineurin-NFAT axis, whereas in non-lymphoid cells, such as kidney epithelial cells, CsA induces Calcineurin inhibitor toxicity (CNT). Up to date, it is unknown via which off-targets CsA induces CNT in kidney epithelial cells. Methods: In vitro experiments using a surrogate marker to measure CNT induction as well as in vivo studies with acute CNT, were used in order to elucidate the underlying molecular mechanism. Results: Inhibition of the NFAT axis does not show any nephrotoxicity. However, inhibition of p38 and PI3K/Akt Kinases showed induction of nephrotoxicity. Conclusions: These findings show that CsA acts NFAT independent on kidney epithelial cells. Moreover, inhibition of certain protein kinases mimic CsA activity on kidney epithelial cells indicating that p38 and PI3K/Akt kinase pathways might be involved in CNT progression on kidney epithelial cells.